Transforming MSMEs Towards Sustainable Growth: A Study of Economic Empowerment - Dinata, Amet Candra; Octavian, Yayan; Sukresna, I Made; Mahfudz (LifeSciFi, 2024)
Empowering the regional economy as an economic foundation through the development of Micro, Small and Medium Enterprises (MSMEs) play a strategic role in promoting inclusive and sustainable economic growth at the regional level. This research aims to examine the success of MSMEs in Pasar Badung and analyze MSME development strategies to enhance local economic empowerment. The study employs a descriptive approach to analyze workforce trends in MSMEs during the 2020-2023 period, with data collection through in-depth interviews with MSME actors and relevant stakeholders. The findings reveal that MSMEs in Pasar Badung face various challenges in their development, including resource limitations, restricted market access, and resistance to change. Nevertheless, through strengthening human resource capacity and implementing appropriate marketing strategies, MSME actors can overcome these challenges and achieve sustainable growth. This research contributes to understanding the significance of MSMEs in strengthening local economies and regional development. The study also emphasizes the urgency of empowerment policies and programs that can drive MSME growth and improve community welfare.